Orthodontic induced inflammatory root resorption : the process involved and its management – a review of literature - Tan, Steven Jun Hong; Farinawati Yazid; Nurfathiha Abu Kasim; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab (Penerbit Universiti Kebangsaan Malaysia, 2022)
Orthodontically induced inflammatory root resorption (OIIRR) is inevitable as the force applied during orthodontic treatment to initiate tooth movement induces inflammation, causing iatrogenic root resorption. Even with the use of new technologies in orthodontic appliances, the traumatic effects on the periodontium are still present. Therefore, a proper understanding of the biological aspect of OIIRR such as its pathophysiology and the repair process is crucial to aid in its prevention or minimizing the damage to the apical region. Reported studies related to root resorption in orthodontics and its management until 2022 were searched electronically via PubMed, Scopus, and Google Scholar using keywords such as ‘root resorption’, ‘orthodontic treatment’, ‘root resorption repair’, and ‘management’. Other sources were taken from the references of the selected papers. The management of OIIRR has not changed much from the past, which is to temporarily stop the active orthodontic treatment for two to three months and a passive archwire can be used instead. However, interventions such as low-level laser therapy (LLLT), low-intensity pulsed ultrasound (LIPUS), and mechanical vibrational force were introduced to reduce the risk or enhance the healing process of OIIRR. Nevertheless, further studies are warranted to develop a proper usage protocol and the long-term effects of these methods.